Technical considerations for cost-effective transposon directed insertion-site sequencing (TraDIS) - Yasuhiro Kyono; Madeline Tolwinski; Stephanie A. Flowers (Scientific Reports, 2024)
Abstract Transposon directed insertion-site sequencing (TraDIS), a variant of transposon insertion sequencing commonly known as Tn-Seq, is a high-throughput assay that defines essential bacterial genes across diverse growth conditions. However, the variability between laboratory environments often requires laborious, time-consuming modifications to its protocol. In this technical study, we aimed to refine the protocol by identifying key parameters that can impact the complexity of mutant libraries. Firstly, we discovered that adjusting electroporation parameters including transposome concentration, transposome assembly conditions, and cell densities can significantly improve the recovery of viable mutants for different Escherichia coli strains. Secondly, we found that post-electroporation conditions, such as recovery time and the use of different mediums for selecting mutants may also impact the complexity of viable mutants in the library. Finally, we developed a simplified sequencing library preparation workflow based on a Nextera-TruSeq hybrid design where ~ 80% of sequenced reads correspond to transposon-DNA junctions. The technical improvements presented in our study aim to streamline TraDIS protocols, making this powerful technique more accessible for a wider scientific audience.